Challenging Social Capital Theory: What Is the Correlation Between Religious Involvement and Civic/Political Engagement? a Case for Chilean Evangelicals [Оспаривая Теорию Социального Капитала: Корреляция Религиозности И Гражданско-Политического Участия Среди Чилийских Евангеликов] - Fediakova, E (Russian Presidental Academy of National Economy and Public Administration, 2021)
This article analyzes the role of Chilean Evangelical and Pentecostal churches in the building social capital, considering its form, and its effects on the socio-political development of civil society and the qual- ity of democratic life. The diversity of the Evangelical field in Chile demands a thorough review of Evangelicals interaction with poli- tics and society. Our results show that Evangelicals and Pentecos- tals, compared to the Catholic population, havehigher involvement in voluntary associations and lower interest in politics. Evangelicals expect their religious authorities to play an active role in the politi- cal field while overall, en masse, they are less involved in politics and less concerned in defining their political identity than their Catholic compatriots. This finding, to some extent, goes against the theory of social capital, which assumes that involvement in religious activities results in increased civic participation in general. Data for the study come from a national sample of Evangelicals (n=754). © 2021 Russian Presidential Academy of National Economy and Public Administration. All rights reserved.